Investigation of the Aerodynamic Characteristics of Platoon Vehicles Based on Ahmed Body - Jianbin Luo; Ke Mi; Dongli Tan; Zhiqing Zhang; Mingsen Li; Jun Qing; Huiqiong Huang (Shock and Vibration)
In this paper, the aerodynamic characteristics of two vehicles and three vehicles in the platoon under different vehicle spacings have been explored in detail. Firstly, the realizable k-ε model was used to verify the numerical method based on a single 35° Ahmed body. Then, the aerodynamic characteristics such as drag characteristics, surface pressure, wake structure, and turbulent kinetic energy distribution were analyzed for the platoon of two and three 35° Ahmed bodies. Although the RANS (Reynolds-averaged Navier–Stokes) model had got good results for simulating a single 35° Ahmed body, when simulating two 35° Ahmed bodies in the platoon, it was found that there is still a big error compared with the experimental data. In the three 35° Ahmed body, the drag coefficient of the leading body is almost unchanged compared with that of the leading body in the two-vehicle platoon, while the drag coefficients of the middle body and the trailing body are both reduced compared with those of the single body. For x/L = 0.25, the middle body is about 56% of the single-body value, and the trailing car is about 88% of the single-body value. It can be seen that the drag reduction effect of three 35° Ahmed bodies is larger than that of two 35° Ahmed bodies. It is shown that the aerodynamic characteristics are very sensitive to the selected platoon vehicle model. Because model with different geometric shapes will produce different wake structures, different aerodynamic phenomena will occur when they are arranged in the platoon.